The death penalty in Zimbabwe: a human rights perspective - Machaya, Musavengana (University of the Western Cape, 2015)
Magister Legum - LLM === There has been an ongoing debate on the abolishment of the death penalty in Zimbabwe. The public, non-governmental organisations and human rights activists need clarity as to the effectiveness, justification and purpose, if any, of the retention of the death sentence in Zimbabwe. Therefore, this paper shall give an insight on whether or not the decision to retain the death penalty in Zimbabwe is line with the country’s international and regional mandate of protecting and promoting human rights.